An observational comparative study of intraocular pressure changes in post-operative cataract patients treated with dexamethasone, difluprednate and prednisolone in a tertiary care centre - Hingorani, Sadhana K.; Desai, Anupama S.; Shastri, Manisha B. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Cataract is opacity of lens which is treated surgically. Topical corticosteroids are routinely used in the treatment of post-operative inflammation following cataract surgery. This study aims to compare the intraocular pressure changes caused by various topical steroids (prednisolone, dexamethasone and difluprednate) in post cataract patients. To compare compliance and to detect any significant adverse effects. Methods: Patients admitted in ophthalmology department for cataract surgery operated by phacoemulsification were taken as subjects. Total number of patients enrolled in the study were 354. Subjects were separated into 3 groups depending on topical steroids which were prescribed after surgery: group 1 - difluprednate, group 2 -dexamethasone and group 3 - prednisolone. Changes in intraocular pressure (IOP) of patients were measured by ophthalmology department preoperatively and postoperatively after 1st, 2nd, 3rd, 4th week of surgery. These data were collected and analysed. Adverse effects, Compliance of patients and number of bottles of drug used after surgery were also noted. Results: On comparing IOP, there was significant variation (p<0.027) between 3 drugs after one week of drug administration. When group 1 was compared with group 2 or group 3 there was no significant difference Average cost of difluprednate is about 3 times higher than the cost of dexamethasone or prednisolone. Conclusions: All the three topical steroids cause a rise in intraocular pressure in post cataract patients. But in group 1 (difluprednate) there was a rise in IOP up to three weeks after surgery but after 3rd week IOP remained stable. Adverse effects were seen more in group 2 and group 3.